Alterações climáticas e o impacto no mix energético em Portugal - Carlos Eduardo Pires da Silva (2018)
Global Climate change is nowadays a very important theme due to its impacts on natural systems and consequently on human development.Eletric Sector is a major contributor for the climatic change phenomenon, but it ir also onde of the most affected by it, due to its high dependence on climate-related natural resources, especially the renewable sources. Eletric production usually means greenhouse effect gases emission into the atmosphere, affecting the climate and therefore the potencial for production from renweable sources. Less reneweable production results in more emission. So it is imperative to break this negative cycle in order to mitigate its effects on the planet.This thesis aims to estimate the effects of climate change on the portuguese energy mix in the medium/long term (until 2050). The proposed methodology uses the past climateric evolution and historical data realted to installed capacity by type in order to relate the energy mix with the installed capacity and the climatic variables. It was developed a prediction model based on climate change projections and predicted installed capacity by type, which will predict the behaviour of the eletric system until 2050 according to 4 different scenarios.The best results were obtained by the scenarios that indicate that a fully renewable electricity system will be possible in the medium term, guaranteeing very low emissions in compliance with the objectives of the European Union. To achieve this, investment in renewables sources must increase considerably.